Site-selective protonation of the one-electron reduced cofactor in [FeFe]-hydrogenase. Issue 10 (25th February 2021) - Laun, Konstantin; Baranova, Iuliia; Duan, Jifu; Kertess, Leonie; Wittkamp, Florian; Apfel, Ulf-Peter; Happe, Thomas; Senger, Moritz; Stripp, Sven T.
Abstract : Hydrogenases are bidirectional redox enzymes that catalyze hydrogen turnover in archaea, bacteria, and algae. Abstract : Hydrogenases are bidirectional redox enzymes that catalyze hydrogen turnover in archaea, bacteria, and algae. While all types of hydrogenase show H2 oxidation activity, [FeFe]-hydrogenases are excellent H2 evolution catalysts as well. Their active site cofactor comprises a [4Fe–4S] cluster covalently linked to a diiron site equipped with carbon monoxide and cyanide ligands. The active site niche is connected with the solvent by two distinct proton transfer pathways. To analyze the catalytic mechanism of [FeFe]-hydrogenase, we employ operando infrared spectroscopy and infrared spectro-electrochemistry. Titrating the pH under H2 oxidation or H2 evolution conditions reveals the influence of site-selective protonation on the equilibrium of reduced cofactor states. Governed by p K a differences across the active site niche and proton transfer pathways, we find that individual electrons are stabilized either at the [4Fe–4S] cluster (alkaline pH values) or at the diiron site (acidic pH values). This observation is discussed in the context of the complex interdependence of hydrogen turnover and bulk pH.